Monetary policy, credit institutions and the bank lending channel in the euro area - Carlo Altavilla; Desislava C. Andreeva; Miguel Boucinha; Sarah Holton (European Central Bank (ECB), 2019)
As the euro area has a predominantly bank-based financial system, changes in the composition and strength of banks' balance sheets can have very sizeable implications for the transmission of monetary policy. This paper provides an overview of developments in banks' balance sheets, profitability and risk-bearing capacity and analyses their relevance for monetary policy. We show that, while the transmission of standard policy interest rate cuts to firms and households was diminished during the crisis, in a context of financial market stress and weak bank balance sheets, unconventional monetary policy measures have helped to restore monetary policy transmission and pass-through to interest rates. We also document the extent to which these non-standard measures were successful in stimulating lending and which bank business models were more strongly affected. Finally, we show that the estimated impact of recent monetary policy measures on bank profitability does not appear to be particularly strong when all the effects on the macroeconomy and asset quality are taken into account.
Keywords: G21; G20; E52; E43; 330; monetary policy; interest rates; banks; credit